Effects of end groups and entanglements on crystallization and melting behaviors of poly(ε-caprolactone). Issue 12 (15th March 2023) - Zhu, Liuyong; Li, Jingqing; Li, Hongfei; Liu, Binyuan; Chen, Jizhong; Jiang, Shichun
Abstract : Melting of the metastable semicrystalline structure of PCL with restricted dynamics is a multistep evolution process involving multiple nanoscale crystalline structures. Abstract : The topology including end groups, entanglement loops, and tie molecules has a significant impact on the rheological and crystallization behavior and consequently on the functionality of a polymer. Unentangled, weakly entangled, and strongly entangled poly(ε-caprolactone)s (PCLs) with end groups and various molecular weights were synthesized. POM and DSC were used to observe spherulite growth and characterize thermal properties during crystallization and melting. The viscosity and structure of the samples were probed by rheology and X-ray analysis, respectively. The crossover of the scaling relationship of viscosity vs molecular weight demonstrates that the samples cover a wide range of entanglement density, and the bulky end groups cause deviations from the classical scaling laws. In situ simultaneous SAXS/WAXS investigations showed that the crystal structure of PCLs did not change with end groups and heating. The results of POM and DSC imply that the end groups and entanglements affect the crystallization rate and the spherulite morphology. The melting of PCLs containing end groups was found to be a multi-step process involving various nanoscale crystalline structures. The evolution of nanoscale crystalline structures of isothermally crystallized PCLs during heating was analyzed by fitting 1D SAXS profiles, and the continuous structural evolution was found to be a process influenced by end groups and entanglements. The results show that end groups and entanglements affect the chain dynamics and lead to constrained crystallization behavior and the formation of metastable structures, ultimately affecting the structure evolution during melting.